Sexual Harassment and Management Behaviour at the Workplace - Vasudevan, Loshinee; Mahadi, Nomahaza (IIUM Journal of Case Studies in Management, 2019)
This paper aims to unravel the personality attributes of victims and perpetrators of sexual harassment that had occurred at the workplace. It also discusses how the issue of sexual harassment can be resolved and how proper policy strategies can be implemented at the workplace. A social-metric method was used to collect and analyse data. The results showed that victims were endowed with a moderate level of the personality attributes while perpetrators were generally endowed with low level personality attributes such as being uncomfortable most of the time, being less confident and they have less self-worth.